Bactericidal Activity of Non-Cytotoxic Cationic Nanoparticles against Clinically and Environmentally Relevant Pseudomonas spp. Isolates - Anna Maria Schito; Gabriella Piatti; Debora Caviglia; Guendalina Zuccari; Alessia Zorzoli; Danilo Marimpietri; Silvana Alfei (MDPI AG, 2021)
Difficult-to-treat bacterial infections caused by resistant human and plant pathogens severely afflict hospitals, and concern the agri-food sectors. Bacteria from the Pseudomonadaceae family, such as P. aeruginosa, P. putida, P. fluorescens, and P. straminea, can be responsible for severe nosocomial infections in humans. P. fragi is the major cause of dairy and meat spoilage, while P. syringae can infect a wide range of economically important plant species, including tobacco, kiwi, and tomato. Therefore, a cationic water-soluble lysine dendrimer (G5-PDK) was tested on several species of Pseudomonas genus. Interestingly, G5-PDK demonstrated variable minimum inhibitory concentrations (MICs), depending on their pigment production, on Pseudomonas aeruginosa (1.6-> 6.4 µM), MICs = 3.2-6.4 µM on P. putida clinical isolates producing pyoverdine, and very low MICs (0.2-1.6 µM) on strains that produced non-pigmented colonies. Time-kill experiments established the rapid bactericidal activity of G5-PDK. In the cytotoxicity experiments on human keratinocytes, after 4 h of treatment with G5-PDK at concentrations 16-500 × MIC, more than 80% of viable cells were observed, and after 24 h, the selectivity indices were maintained above the maximum value reported as acceptable. Due to its proven bactericidal potency and low cytotoxicity, G5-PDK should be seriously considered to counteract clinically and environmentally relevant Pseudomonas isolates.